Uji Fitokimia dan Aktifitas Anti Bakteri Ekstrak Media Supernatan Bakteri Simbion Vibrio sp. Gastropoda Oliva vidua Terhadap Bakteri Multi Drug Resistant - Harmawan, Adityo; Ridho, Ali; Pringgenies, Delianis (977-2407769)
The development of antibiotic resistance has become an important issue in medicine. Many types of bacteria are pathogenic to humans were reported to have become resistant to one or more types of antibiotics. It is pushing for a new search for alternative sources of antibiotic-producing compounds. One source of potential alternatives to be developed as a source of new antibiotic compound s are symbiotic bacterium with gastropods. The purpose of this study was to determine the characteristics of bacterial symbionts in gastropods ( TOV 12.16 bacterial isolates), the bioactivity of crude bacterial extracts against bacterial MDR and find a group of compounds from TOV 12.16 crude bacterial extracts which most potentially. The main materials used in this study were samples of bacterial isolates TOV 12.16 in isolation from the gastropods (Oliva vidua) from Aquatic Ternate (North Maluku). While the bacterium MDR test are Escherichia coli and Staphylococcus aureus obtained from the Laboratory of Microbiology Faculty of Medicine UNDIP. Biochemical tests used to determine the characteristics of bacterial isolates TOV 12.16. Meanwhile, to identify the bioactive compounds using phytochemicals screening and GC/MS. Bacterial symbionts Oliva vidua Gastropoda is Vibrio ordalii. Ethyl acetate crude extract of bacterial symbionts Oliva vidua Gastropoda species showed antibacterial activity of the most active against MDR bacteria test. Phytochemical screening test results showed the ethyl acetate crude extract showed two groups of compounds which contain flavonoids and triterpenoid compound that has both the antibacterial activity. Being on the analysis of the GC/MS_are_known_isobutyric_acid_and_2-metilbutanoic_acid.